Identification of atrial‐enriched lncRNA Walras linked to cardiomyocyte cytoarchitecture and atrial fibrillation. Issue 1 (3rd December 2021) - García‐Padilla, Carlos; Domínguez, Jorge N.; Lodde, Valeria; Munk, Rachel; Abdelmohsen, Kotb; Gorospe, Myriam; Jiménez‐Sábado, Veronica; Ginel, Antonino; Hove‐Madsen, Leif; Aránega, Amelia E.; Franco, Diego
Abstract: Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia in humans. Genetic and genomic analyses have recently demonstrated that the homeobox transcription factor Pitx2 plays a fundamental role regulating expression of distinct growth factors, microRNAs and ion channels leading to morphological and molecular alterations that promote the onset of AF. Here we address the plausible contribution of long non‐coding (lnc)RNAs within the Pitx2>Wnt>miRNA signaling pathway. In silico analyses of annotated lncRNAs in the vicinity of the Pitx2, Wnt8 and Wnt11 chromosomal loci identified five novel lncRNAs with differential expression during cardiac development. Importantly, three of them, Walaa, Walras, and Wallrd, are evolutionarily conserved in humans and displayed preferential atrial expression during embryogenesis. In addition, Walrad displayed moderate expression during embryogenesis but was more abundant in the right atrium. Walaa, Walras and Wallrd were distinctly regulated by Pitx2, Wnt8, and Wnt11, and Wallrd was severely elevated in conditional atrium‐specific Pitx2‐deficient mice. Furthermore, pro‐arrhythmogenic and pro‐hypertrophic substrate administration to primary cardiomyocyte cell cultures consistently modulate expression of these lncRNAs, supporting distinct modulatory roles of the AF cardiovascular risk factors in the regulation of these lncRNAs. Walras affinity pulldown assays revealed its association with distinct cytoplasmic and nuclear proteins previously involved in cardiac pathophysiology, while loss‐of‐function assays further support a pivotal role of this lncRNA in cytoskeletal organization. We propose that lncRNAs Walaa, Walras and Wallrd, distinctly regulated by Pitx2>Wnt>miRNA signaling and pro‐arrhythmogenic and pro‐hypertrophic factors, are implicated in atrial arrhythmogenesis, and Walras additionally in cardiomyocyte cytoarchitecture.